(-6x+46)+(-9x+29)=180

Simple and best practice solution for (-6x+46)+(-9x+29)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-6x+46)+(-9x+29)=180 equation:



(-6x+46)+(-9x+29)=180
We move all terms to the left:
(-6x+46)+(-9x+29)-(180)=0
We get rid of parentheses
-6x-9x+46+29-180=0
We add all the numbers together, and all the variables
-15x-105=0
We move all terms containing x to the left, all other terms to the right
-15x=105
x=105/-15
x=-7

See similar equations:

| 495=165+55m | | -8x+8=−8x+8 | | 20+(4x-6=6x | | 0=4+w/5 | | 5x+10=3x+2x-8 | | 5z=-8+6z | | x+5=(x–2)–(2x–7 | | -3(x+5+3x)-5(x+5+3x)=24 | | w-2=6.5 | | -354=6(8r-3) | | 3/4z+5=25 | | 2-(3x-3)=5x-3 | | 14-7(9v+3)=13v+41​ | | 7x-6=18-6x | | -2=-5x+24 | | 12x(4-3)=4(6x+4)-4 | | 6x-(3x+4)=4x-39 | | 1/2x-3/4=5/3 | | 5(2x+7)=-11+16 | | N/10n=5n+10 | | 3x-2+7x+4=4x+28 | | -7.9x+2.3=6.62-7.4x | | x−6x+4−10x=34 | | -3x+144x-8=-(-8+18) | | 29−(x+7)=5x−2 | | -10x=11-9x | | 5x+8x+2=28 | | -5(x+3)=-8(x-6) | | x+4+x-1*2=x+5+x+5+x-1 | | (6m+8)=4(17−m | | -2=5x+24 | | -10+3x=4x-6 |

Equations solver categories